TRANSFORMASI NOVEL ANANTA PRAHADI KARYA RISA SARASWATI KE FILM ANANTA SUTRADARA RIZKI BALKI (KAJIAN EKRANISASI) - Parura, Mery (Fakultas Bahasa dan Sastra Indoensia, 2020)
This study aims to describe the forms of ekranisasi that experience shrinkage, addition, and change in variations in the categories of intrinsic elements, plot, figures, and settings. The research method used is descriptive qualitative. The results of this study indicate that the form of ekranisasi in the form of shrinkage, addition, and change variations occur in the category of intrinsic elements of the plot, character, and background. The ekranisai process that often happens is shrinking. This resulted in changes and differences in novels and films. Based on the results of the study, it can be concluded that the ekranisasi process occurs because of the elements that are considered not important and impossible to visualize, consideration of the duration, as well as consideration of commercial aspects.